Fertility after cytoreductive surgery and hyperthermic intraperitoneal chemotherapy: A call to action. Issue 4 (26th January 2021) - Violette, Caroline; Kim, Tesia; Shandley, Lisa; Lee, Rachel; Staley, Charles; Winer, Joshua; Maithel, Shishir; Hipp, Heather; Kawwass, Jennifer; Russell, Maria
Abstract: Introduction: Cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) is increasingly accepted as the best therapeutic option in primary and some secondary peritoneal malignancies. The ramifications of this procedure on fertility are unknown. The aim of this study was to assess the current association of CRS/HIPEC with fertility following surgery. Methods: A review of patients who underwent CRS/HIPEC between 2009 and 2018 was performed. Female patients were included if they were between ages 18–50 at the time of surgery. Gynecologic and obstetric history before and following CRS/HIPEC was collected by phone interview. Results: Of 48 eligible participants, 21 completed the survey. Sixty‐five percent of women underwent a total abdominal hysterectomy before or during CRS. Twenty‐nine percent of these women recall fertility counseling before CRS/HIPEC, while 14.3% saw a fertility specialist for consultation, and only one patient proceeded with oocyte cryopreservation before treatment. There were no pregnancies reported following treatment with CRS/HIPEC. Conclusion: Few patients after CRS/HIPEC retain child‐bearing potential, partly due to the high rate of hysterectomy and oophorectomy at time of surgery. Efforts towards improved preoperative counseling, increased oocyte cryopreservation, and evaluating the safety of preserving reproductive organs at the time of surgery are needed.